AGE AND GROWTH OF POLYNEMUS HEPTADACTYLUS CUV. AND VAL. FROM THE BOMBAY-SAURASHTRA REGION - Kagwade, P V (Indian Journal of Fisheries, 2011)
The age and growth of Polynemus heptadactylus ware studied from the lengthfrequency distribution and by the annulus method using scales and otoliths. The lengthsattained at the end of first through eighth years of life are 83 mm, 128 mm, 158 mm,188 mm, 213 ram, 237 mm, 255 rnm and 273 mm respectively as deduced from the lengthfrequency method. The studies on annuli revealed identical results for the first fouryears of life. A 'larval ring' found on the otoliths of fish of above 26 mm was notpresent on the scales. The causes of formation of annuli are not known at present